STRATEGI PEMBELAJARAN KOLABORATIF BERBASIS MODEL PROBLEM BASED LEARNING (PBL) PADA PENDIDIKAN PANCASILA KELAS II SEKOLAH DASAR - Sri Wahyuni; Ahmad Muhibbin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to analyze the application of collaborative learning strategies based on the Problem Based Learning (PBL) model in Pancasila Education in the second grade of elementary school, especially on the topic of “Pancasila Emblem”, chapter 2: “I Behave Pancasila”. This research used a qualitative approach with a case study design in one of the elementary schools in Mojogedang District with 20 students. Data collection techniques include observation, interview, and documentation. The results showed that PBL-based collaborative learning strategies were effectively applied to Pancasila education subjects in elementary schools, students were enthusiastic and active in working together in groups, more confident in communication skills and solving problems related to the Pancasila symbol and had a positive impact on in-depth understanding of the material, critical thinking skills, collaboration, and getting optimal learning outcomes. In addition, it also deepens the character of students in accordance with the values of Pancasila, such as mutual cooperation and global diversity and strengthens the relevance of the PBL model as a suitable learning method to be applied in elementary school Pancasila education subjects.